A review of the genus Rhimphoctona Förster, 1869 (Hymenoptera: Ichneumonidae: Campopleginae) from the Ukrainian Carpathians, with a key to European species - Varga, Oleksandr (Zootaxa, 2017)
Seven species of Rhimphoctona Förster, 1869: R. longicauda Horstmann, 1980, R. megacephalus (Gravenhorst, 1829), R. obscuripes (Holmgren, 1860), R. pectoralis (Kriechbaumer, 1890), R. rufocoxalis (Clément, 1924), R. teredo (Hartig, 1847), R. xoridiformis (Holmgren, 1860) are recorded from the Ukrainian Carpathians. All species, except R. megacephalus, are recorded from Ukraine for the first time. The following synonymy is established: Rhimphoctona pectoralis = R. maiator Aubert, 1986 syn. nov. An illustrated key to all European Rhimphoctona species is provided.